Faculty Senate, Minutes, May 17, 2012 - Faculty Senate, Valdosta State University (Valdosta, Ga.: Valdosta State University Archives and Special Collections)
Faculty Senate, Minutes, May 17, 2012. Chairperson, Louis Levy; Vice Chairperson, Philip Gunter; Executive Secretary, Tracy Woodard-Meyers; Parliamentarian, Ed Walker;
1 electronic record. Valdosta State University. Faculty Senate, Minutes, May 17, 2012. 4 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records